ANALISIS PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI DENGAN MENGGUNAKAN MODEL ALTMAN, OHLSON DAN SPRINGATE - DEWI INDAH SARI; MICHAEL HADJAAT; M. AMIN KADAFI (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
This study aims to determine the results of prediction of financial distress in the food and beverage company using Altman model, Ohlson and Springate in the period 2012-2014 for financial data obtained from the Indonesia Stock Exchange. This study using purposive sampling techniques and the results there are 12 companies that meet the criteria. The results using Altman model years 2012- 2014 there is one company that is experiencing financial distress. Then the prediction results by using models Ohlson in 2012  there  was  one  company  predicted  financial  distress.  In  2013  there  were experiencing  financial  distress  and  in  2014  there  are  two  companies  predicted  to experience  financial  distress.  The  next  prediction  results  by  using  the  model  years 2012-2014 Springate there are 2 companies experiencing financial distress.Keywords: Financial distress, Altman, Ohlson, Springate, Bankruptcy